Effectiveness of Murottal Therapy in Reducing Anxiety in Diabetics - Siti Nur Asiyah; Imamah Istikhomah (Journal of Health Science and Prevention, 2019)
The purpose of this study was to determine the effectiveness of murottal Al-Qur’antherapy in reducing anxiety in people with diabetes mellitus. This research is quantitative research with experimental methods that use data collection techniques in the form of anxiety scale. Subjects in this study amounted to 15 people who underwent in a patient at RSUD dr. H. Slamet Martodirdjo Pamekasan with criteria of people with diabetes mellitus who have high anxiety. Selection of subject by giving an anxiety scale to everyone with diabetes mellitus who is undergoing hospitalization in hospitals in October. The results of the scale calculation and then made the norm with the formula interval to categorize the anxiety of high and low. Of the 15 people who were selected to be the subjects of the past research will undertake the murottal Al-Qur’an treatment. The result is effective in reducing anxiety in people with diabetes mellitus.